Analysis of Student Satisfaction with the Digital System for Using the Chemistry Department Room at State University of Medan - Ridho, Dimas; Pratiwi, Alfira Julian; Kurniawan, Ekin Dwi Arif; Ardila, Mutia; Samosir, Rafidah Almira; Nur, M Rosyadi Izzuddin (Holistic Science, 2024)
This study aims to determine student satisfaction with the digital system of room usage at the Chemistry Department, State University of Medan. The research method used is descriptive qualitative. The results of the study conducted on 25 students showed that in the aspect of recording room usage, there was an increase in satisfaction of 7.7%, in the aspect of room usage recapitulation, there was an increase in satisfaction to very good with a percentage of 53.8%, in the aspect of viewing room availability, there was an increase in satisfaction to very good with a percentage of 46.2%, in the aspect of viewing lecturers' schedules, there was an increase in satisfaction to very good with a percentage of 53.8%. Based on the results of the study, it shows that the response to satisfaction with the digital system shows an increase in satisfaction to improve the quality of room usage at the Chemistry Department, State University of Medan.